Pilot study of combined FDG‐PET and dynamic contrast‐enhanced CT of locally advanced cervical carcinoma before and during concurrent chemoradiotherapy suggests association between changes in tumor blood volume and treatment response. (2nd July 2018) - Banks, Thomas I.; von Eyben, Rie; Hristov, Dimitre; Kidd, Elizabeth A.
Abstract: Modern PET/CT radiotherapy simulators offer FDG‐PET and dynamic contrast‐enhanced (DCE) CT imaging for combined volumetric assessment of tumor metabolism and perfusion. However, the clinical utility of such assessment has not been clearly defined. Thus, in a prospective longitudinal study of primary cervical tumors treated with concurrent chemoradiotherapy (CCRT) we evaluated: (1) whether PET and perfusion parameters correlate or provide complementary information; (2) what imaging changes occur during CCRT; and (3) whether any parameters are predictive of treatment response as assessed by PET/CT 3 months posttherapy. FDG‐PET/CT and DCE‐CT scans were performed on 21 patients prior to and during CCRT. Coregistered volumetric parametric maps of standardized uptake value (SUV) measures and perfusion parameters blood flow (BF), blood volume (BV), and permeability were generated. Summary statistics for these parameters and their changes were calculated within the metabolic tumor volume (MTV). Correlations between SUV and BF/BV/permeability on local and global bases were assessed with Pearson's coefficient r . MTV, maximum SUV, and mean SUV decreased significantly between the pre‐ and during‐treatment time points, while mean BV and permeability increased significantly. Global correlations between mean BF/BV/permeability and mean SUV values (−.15 <  r  < .29) were at most moderate. An increase in mean tumor BV during treatment was significantly correlated with complete metabolic response on 3‐month posttreatment PET/CT. Weak correlations of SUV and perfusion parameters suggest a complementary role of FDG‐PET and DCE‐CT for tumor characterization. The association between relative change in mean BV and outcome suggests a potential role for DCE‐CT in early evaluation of cervical tumor response to chemoradiotherapy. Abstract : A prospective pilot study of combined FDG‐PET and dynamic contrast‐enhanced (DCE) CT imaging of primary cervical tumors before and during concurrent chemoradiation finds weak correlations between metabolic and perfusion parameters, suggesting a complementary role of FDG‐PET and DCE‐CT imaging for tumor characterization. Concurrent chemoradiation results in significant changes in metabolic and perfusion parameters and the association between relative change in mean blood volume and treatment outcome suggests a potential role for DCE‐CT in early evaluation of cervical tumor response to chemoradiotherapy .